2010
DOI: 10.1001/archophthalmol.2011.72
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Visual Field Progression in Treated Glaucoma

Abstract: To determine intraocular pressure (IOP)dependent and IOP-independent variables associated with visual field (VF) progression in treated glaucoma. Design: Retrospective cohort of the Glaucoma Progression Study. Methods: Consecutive, treated glaucoma patients with repeatable VF loss who had 8 or more VF examinations of either eye, using the Swedish Interactive Threshold Algorithm (24-2 SITA-Standard, Humphrey Field Analyzer II; Carl Zeiss Meditec, Inc, Dublin, California), during the period between January 1999 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
224
6
6

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(254 citation statements)
references
References 57 publications
16
224
6
6
Order By: Relevance
“…Still, several studies, both prospective and retrospective, have derived estimates of average rate of VF loss in groups of patients. [1][2][3] Indeed, knowledge of the distribution of rates of loss in populations as defined by mean deviation (MD) loss per year, where MD is a commonly used metric for assessing severity of VF loss, is clinically useful information. Recent studies, using data from treated patients in routine care, have yielded estimates for median rate of MD loss that vary considerably from − 0.05 to − 0.62 dB/year.…”
Section: Introductionmentioning
confidence: 99%
“…Still, several studies, both prospective and retrospective, have derived estimates of average rate of VF loss in groups of patients. [1][2][3] Indeed, knowledge of the distribution of rates of loss in populations as defined by mean deviation (MD) loss per year, where MD is a commonly used metric for assessing severity of VF loss, is clinically useful information. Recent studies, using data from treated patients in routine care, have yielded estimates for median rate of MD loss that vary considerably from − 0.05 to − 0.62 dB/year.…”
Section: Introductionmentioning
confidence: 99%
“…Differences in the definition of visual field progression may also explain the disparities between our results. Previous studies 20,[35][36][37][38] have shown that different progression criteria do not necessarily identify the same eyes as progressing. The study by Medeiros and colleagues defined SAP progression using an event analysis derived from the Early Manifest Glaucoma Trial 39 consisting of a change in three or more of the same test points on three follow-up consecutive tests.…”
Section: Discussionmentioning
confidence: 96%
“…Progression with PLR criteria was defined as 2 contiguous locations in the same hemifield that were losingZ1.0 dB/year with Po0.01. 20,21 All patients had visual fields and OCT imaging performed on the same day. The average number of visual fields included in the progression analysis was 9.75 ± 2.2 (range 5-15) for each patient.…”
Section: Oct Imaging and Analysismentioning
confidence: 99%
“…Although it is a well-established clinical fact that very high intraocular pressure (IOP), higher than blood perfusion pressure, is able to induce ischemic damage [18], the presence of glaucomatous changes in patients with moderately increased, normal or even low pressure, without demonstrable pressure spikes, cannot be directly attributed to pressure, and thus additional explanations have been sought [19]. Raised intraocular pressure has been discarded as "the" causative factor and now ranks alongside other risk factors.…”
Section: Glaucoma: How Many Different Diseases?mentioning
confidence: 99%